Elucidating Lineage-Specific Myelotoxicity and Chromosomal Abberation Status in Hydroquinone-Exposed Hematopoietic Stem / Progenitor Cells - Julia Mohd Idris (Life Sciences, Medicine and Biomedicine, 2018)
Benzene exposure has been associated with hematotoxicity and leukemogenicity. However, the impact of benzene exposure on complex microenvironment of Hematopoetic Stem Cells (HSCs) niche, comprising of HSCs and lineage-specific progenitors remains elusive. Thus, a study on benzene-targeting HSCs niche could uncover mechanism linking benzene to HSCs niche alteration. This study evaluates the lineage-specific responses following exposure to a benzene metabolite, namely hydroquinone (HQ) in targeting HSCs and myeloid-committed progenitors. Freshly isolated murine bone marrow cells (BMCs) were exposed to HQ at series of concentrations (0 – 50 µM) for 24 hours; followed by cell viability analysis using MTT assay. Chromosomal aberration (CA) status was determined using karyotyping analysis. Expression of surface antigen for HSCs (Sca-1) was confirmed by flow cytometer. Lineage-specific myelotoxicity was studied using the colony-forming unit (CFU) assay for the following myeloid progenitors: CFU granulocyte /erythrocyte /macrophage /megakaryocyte (CFU-GEMM), CFU-granulocyte/macrophage (CFU-GM), CFU-granulocyte (CFU-G), CFU-macrophage (CFU-M), CFU-erythroid (CFU-E) and Burst-forming unit erythroid (BFU-E). HQ reduced (p<0.05) viability of BMCs at 25 µM and 50 µM with the IC10, IC25, and IC50 were at 17 µM, 23 µM and 35 µM, respectively. Increased (p<0.05) frequency of CA was observed in HQ-treated group as compared to control. Reduced (p<0.05) Sca-1+ cells at 17 µM, 23 µM and 35 µM indicates cytotoxic effect of HQ targeting HSCs population. Reduced (p<0.05) total colony counts were noted following HQ exposure at 6.25 µM and a complete inhibition of colony growth were observed at higher concentration (12.5 µM). HQ reduced (p<0.05) the growth of CFU-GEMM, CFU-GM and CFU-G at 6.25 µM, while the growth of CFU-M, CFU-E and BFU-E were not remarkably affected at lower concentrations (1.56 µM and 6.25 µM). Conclusively, HQ induces chromosomal aberration and cytotoxicity on HSCs with notable lineage-specific responses in governing benzene-mediated myelotoxicity targeting HSCs niche.